Quality control of certain slimming herbal products present in the Egyptian market - Nermin Abdelwahab Mahmoud Eissa; Amira Ahmed Abdelmotaal; Eman Gaber Haggag; Mostafa Aly Abdelkawy (Cairo : Nermin Abdelwahab Mahmoud Eissa, 2012)
The evaluation of two commercial slimming herbal teas was carried out by comparing them to prepared standard herbal mixtures. Quality control of the herbal tea preparations was conducted through microscopical identification of their diagnostic elements. GCMS of the volatile oil constituents. HPLC quantitative estimation of the main active constituents as well as the bioactivities of the teas
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Herbal teas; Quality control; Slimming